Reverse Archaeology: A New Method - Paolo Rosati (Proceedings)
Reverse Archaeology is a digital method useful for rebuilding an old excavation from its documentation. It mainly involves passing data from analogical sheets to digital feature/tables or from older sources to new and open-source formats. The idea for this paper came from the Una Quantum 2021 conference, specifically from the writing of the paper presented with Agnese Vacca at that same conference. What will be presented in this paper is a new assessment, with some other examples and a larger theoretical support, toward the creation of a community and a practical manual.